ROS mediated antibacterial activity of photoilluminated riboflavin: A photodynamic mechanism against nosocomial infections. (2019) - Khan, Saniyya; P, Mohammed Rayis; Rizvi, Asim; Alam, Md. Maroof; Rizvi, Meher; Naseem, Imrana
Highlights: Riboflavin undergoes intersystem conversion under photoillumination. Interacts with molecular oxygen and generates ROS. Generated ROS disrupts E. coli cell membranes. Ultimately killing E. coli . Mechanism can be used to kill E. coli on hospital ware causing nosocomial infections. Abstract: Nosocomial infections are a major threat to modern therapeutics. The major causative agent of these infections is multidrug-resistant gram-negative bacteria, which impart high morbidity and mortality rate. This has led to an urge for the development of new antibiotics. Antimicrobial photodynamic therapy is a promising strategy to which till date no resistant strain has been reported. Since the efficacy of photodynamic therapy largely depends on the selection and administration of an appropriate photosensitizer, therefore, the realization of clinically active photosensitizers is an immediate need. Here, by using E. coli as a study model we have demonstrated the antimicrobial photodynamic potential of riboflavin. Intracellular ROS formation by DCFH-DA assay, lipid peroxidation, protein carbonylation, LDH activity was measured in treated bacterial samples. Enzymatic (SOD, CAT, GSH) antioxidants and non-enzymatic (GSH) was further evaluated. Bacterial death was confirmed by colony forming assay, optical microscopy and scanning electron microscopy. The treated bacterial cells exhibited abundant ROS generation and marked increment in the level of oxidative stress markers as well as significant reduction in LDH activity. Marked reduction in colony forming units was also observed. Optical microscopic and SEM images further confirmed the bacterial death. Thus, we can say that photoilluminated riboflavin renders the redox status of bacterial cells into a compromised state leading to significant membrane damage ultimately causing bacterial death. This study aims to add one more therapeutic dimension to photoilluminated riboflavin as it can be effectively employed in targeting bacterial biofilms occurring on hospital wares causing several serious medical conditions.